2022
DOI: 10.1136/gutjnl-2022-328166
|View full text |Cite
|
Sign up to set email alerts
|

Advancing human gut microbiota research by considering gut transit time

Abstract: Accumulating evidence indicates that gut transit time is a key factor in shaping the gut microbiota composition and activity, which are linked to human health. Both population-wide and small-scale studies have identified transit time as a top covariate contributing to the large interindividual variation in the faecal microbiota composition. Despite this, transit time is still rarely being considered in the field of the human gut microbiome. Here, we review the latest research describing how and why whole gut a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
121
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(127 citation statements)
references
References 226 publications
3
121
2
1
Order By: Relevance
“…Studies from the 1970s already showed that ECs can have profound impact on gut motility [17,28,29]. Current evidence suggests that gut transit time affects the gut microbial composition and function [30]. Here we found that concentration of ECs varied between proximal (V1) and distal colon (V4).…”
Section: Discussionsupporting
confidence: 53%
“…Studies from the 1970s already showed that ECs can have profound impact on gut motility [17,28,29]. Current evidence suggests that gut transit time affects the gut microbial composition and function [30]. Here we found that concentration of ECs varied between proximal (V1) and distal colon (V4).…”
Section: Discussionsupporting
confidence: 53%
“…However, it remains unknown whether enterotypes differ in their capacity to harvest energy from the diet. Moreover, it is not known whether intestinal transit time, which is linked to gut microbial composition, diversity, and metabolism [ 15 – 19 ], is a determinant of microbiota-dependent energy harvest in the gut. Therefore, we investigated whether gut microbial energy extraction, as reflected by dry stool energy density, was associated with intestinal transit time and microbiome community structures in 85 overweight adults.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly dietary ber intake is considered to have a relevant role here because non-digestible carbohydrates are the precursors of SCFA (9). Another potential confounding factor that was not assessed in the current research is gut transit time (54). In addition, it should be noted that fecal and blood samples were not always collected on the same day, since blood sample analysis was part of standard care and depended on individual treatment schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it might be bene cial to include markers of gastrointestinal in ammation (e.g. fecal calprotectin) and gut transit time (54,55).…”
Section: Discussionmentioning
confidence: 99%